Covid-19 pandemic and work from home: Effect on workers productivity - Lau Jeng Hao; Angela Telon Wan; Irene Loh Xia Ling; Lim Pui Hua; Luciana Ding; Mohd Arieef Hafizi Mohd Hashim; Roslinah Mahmud (Universiti Malaysia Sabah, 2021)
Work From Home (WFH) is generally applied to employers and workers during the COVID-19 pandemic. This is one of the government's steps to reduce the transmission of coronavirus disease by restricting physical interaction. This research aims to establish the impact on job efficiency of WFH during the covid-19 pandemic. In this context, WFH is defined as a new approach to work allowed by the internet and accessibility where it can be achieved regardless of the physical location of a person's work. The results indicate that WFH has a positive and negative impact on the productivity of workers. The government should take numerous steps to reduce the adverse effects of WFH among employees.